Accuracy of Spinal Anesthesia Drug Concentrations in Mixtures Prepared by Anesthetists. Issue 8 (7th December 2022) - Heesen, Michael; Steuer, Christian; Wiedemeier, Peter; Schwappach, David
Abstract : Objective: Medication errors include the indirect dosing of drugs. For spinal anesthesia mixtures of local anesthetics, opioids are drawn from ampoules and combined in a syringe, according to clinical practice. We set out to determine the accuracy of the drug mixtures. Methods: Physicians of our department were invited to prepare the mixture used for spinal anesthesia for cesarean section, consisting of 10-mg hyperbaric bupivacaine (2-mL volume), 20-μg fentanyl (0.4-mL volume), and 100-μg morphine (0.1-mL volume). Concentrations of these drugs were determined by means of high performance liquid chromatography. Interindividual and intraindividual variations were assessed. Results: We analyzed 96 samples from 31 physicians. Fifty-one percent of the measured bupivacaine concentrations were in ±10% deviation range of the intended concentration; 17% of the fentanyl and 24% of the morphine concentrations were in this range. A total of 2.1% of the samples had a bupivacaine concentration corresponding to a dose of 8 mg or less, and 11.5% of the samples had a morphine concentration corresponding to a dose of 150 μg or greater. Intraindividual variations were 10.9% for bupivacaine, 24.7% for fentanyl, and 38.9% for morphine. Conclusions: Our results show a high deviation of the obtained from the intended concentrations. Two percent of the samples had bupivacaine concentrations that probably resulted into an insufficient analgesia, and 11% of the samples had morphine concentrations that, according to guidelines, would require a longer monitoring period than with the intended dose.